PRINSIP DASAR PRODUKSI DALAM EKONOMI ISLAM - Misbahul Ali (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
Production and consumption activities are a chain of inter-related to each other. Production activities must be fully in line with consumption activities. The purpose of production is to provide goods and services that can provide the maximum serious benefits for consumers which are realized in the fulfillment of human needs at a moderate level, to find people's needs and their fulfillment, to prepare inventory of goods / services in the future, as well as to meet facilities for social activities and worship to God . In conventional economic concepts (capitalist) production is intended to gain maximum profit. In contrast to the conventional economic production goals production goals in Islam is to provide the maximum benefit for consumers.Although the primary purpose of Islamic economics is to maximize the benefit, profits are not prohibited as long as they are in the goal frame and the Islamic law. It is formulated in the concept of welfare that benefits coupled with blessings.All production detailing activities are tied to the moral value setting and Islamic techniques as well as in consumption activities. Islamic values which are relevant with the production are developed from the three main values in Islamic economy: caliphate, fair and takaful. More specifically these values include such as long-term perspective, keeping promises and contracts, avoiding forbidden things, etc.